Effects of oil palm empty fruit bunch pre-treatments on medium density fibreboard performance - Md Allwi, Norul Izani (2015)
Oil palm industries generate massive quantities of oil palm biomass such as oil palm trunk (OPT), oil palm frond (OPF) and oil palm empty fruit bunch (EFB). Numerous research and development efforts have been undertaken to utilize EFB, concentrating mainly on the production of pulp for paper making,while a handful can also be found on the production of medium density fibreboards (MDF), particleboard, mattress, agricultural mats, high quality organic fertilizer and charcoal briquette. However, the performance of the produced end product sometimes fails to meet the standard. Some researchers have revealed that two critical problem arise in utilizing EFB is its relatively high residual oil content and initial pH level (more alkali) resulting in some adverse effects on the adhesion properties of the fibre in particular when using urea formaldehyde (UF) resin as the binder. In this study, the treatments to remove the residual oil on EFB fibre were done by soaking the fibres in sodium hydroxide (NaOH) for 30 min, boiling the fibres in water for 30 min or a combined soaking in NaOH and boiling water. The effects of treatment on residual oil content and other fibre properties such as adhesion properties, tensile properties, thermal analysis and fibre morphological changes were evaluated. The treated fibres were also used to manufacture MDF using urea formaldehyde (UF) and phenol formaldehyde (PF) as a binder. The mechanical, bonding strength and dimensional stability properties of the panels bonded at three resin level (8, 10 and 12% w/w) were evaluated according to Malaysian Standard 1787 (MS 1787:2005) and the failure characteristics were then determined. The difference behaviour of treated fibre in UF and PF resin curing were briefly discussed. The density profile and its effects on the board’s properties,surface characteristics of MDF from different fibre pre-treatment were also discussed. Generally, NaOH soaking treatment was significantly removed the residual oil in EFB fibre compared to other treatments. The initial pH of EFB fibre (untreated) was 5.66. The pH was increase to be slightly alkali (7.65) after the fibre was soaked in 2%NaOH. Boiling the fibre in water reduced the pH to become more acidic (5.17). The results also showed that the alkali treatment have significant influence on pH, tensile strength and thermogravimetric analysis of EFB. The EFB fibres treated with boiling were apparently more compatible in UF resin with highest modulus of rupture (MOR 33.4 MPa), modulus of elasticity (MOE 2838 MPa) and internal bonding (IB 0.87 MPa). NaOH soaking treated fibre with PF resin bonding resulted in better mechanical and physical properties with the value of 31.4 MPa (MOR), 2437 MPa (MOE) and 0.67 MPa (IB). Basically, dimensional stability, thickness swelling (TS) and water absorption (WA) of both UF and PF resin bonded MDF were lowest in 12% resin level. Generally, the board properties improved with increasing adhesive levels. Resin level was found to have major influences on vertical density profile (VDP), thus affect the mechanical board properties. MOE and MOR were benefited by high density surfaces, while IB and shear strength were improved by higher core density. In this study, positive correlations (R2 from 0.51 to 0.75) were found between IB and core density. The top surface (D1) was positively correlated with MOR (R2 from 0.50 to 0.52), whilst the bottom surface (D3) was positively correlated with MOE (R2 ranging from 0.59 to 0.63). These correlations were found correspondingly in both UF and PFbonded MDF. The overall results indicated that the treatment of fibre on residual oil content changed the fibre pH, thus significantly affect the board properties. The best pre-treatment for EFB is by soaking in NaOH but only if PF is used as a binder, compared to water boiling which is more compatible in UF resin. Since the alkaline or acidic pre-treatment will changes the pH at the fibre surface, the important consideration after pre-treatments being done, is to make sure the final pH of treated fibre is suitable and compatible with appropriate resin used.